Socio-economic status of fisher communities in Dengar beel under Melandah Upazila, Jamalpur, Bangladesh (Asian Journal of Medical and Biological Research, 2021)
The current study was conducted to evaluate the socio-economic profile of fisher communities in Dengar beel under Melandah Upazila of Jamalpur district, Bangladesh. A total of 45 fishers were surveyed from November 2020 to April 2021. It was found that the family size of 53% of fishers was medium, consisting of 5-6 members. Most of the fisher communities belonged to the age group above 45 years old, represented by 100% Muslim. About 73% of fishers were less educated, 13% primary level, 7% secondary level, and 7% Secondary School Certificate passed and above, respectively. Most of the fishers (60%) have katcha houses with tin roofing, 7% have katcha house with straw roofs, 13% have semi- pucca houses and 20% have pucca houses. Around 93% of fishers used their own tube-well while only 7% used neighbours’ tube-well. All of the fisher household were connected with electricity supply. About 27% of fisher communities used katcha toilets, 46% used semi pucca toilets and 27% used pucca toilets. About 47% of fisher communities were dependent on village doctors, 33% got health service from Upazila health complex, 20% from MBBS doctors, and others. About 46% of fishers were engaged in fishing as their primary occupation while 27% in agriculture with fishing, 20% in daily labour with fishing and 7% in livestock rearing. About 33% of the fishers had low income, 40% had medium income and 27% had high income. The present study revealed that the fishers of Dengar Beel were mostly less educated, less privilege to attain modern technology-oriented training experience, less income and less awareness about sanitation and health facilities. So, provide soft loans to fishers, and strengthening people awareness has been might be helpful to improve the socio-economic status of fisher communities in Dengar Beel.Asian J. Med. Biol. Res. 2021, 7 (2), 164-173